Modified office practice in COVID-19 pandemic - an otorhinolaryngologist perspective - Tripathi, Juhi; Kumari, Shweta; Rastogi, Shalabh (International Journal Of Community Medicine And Public Health, 2020)
COVID-19 spreads through contact, minute droplets and aerosol from infected person which may be symptomatic or asymptomatic. Nose and throat had very high load of severe acute respiratory syndrome (SARS-CoV-2) virus. Otorhinolaryngologists by virtue of their work which requires close examination of these part are at very high risk of infection. Many studies are available for precautions to be taken in patient management related to COVID-19 in wards and surgical intervention in operation theaters but very little information is available regarding precautions in working in outpatient clinic setting. Our article highlights some changes we made in ear, nose and throat (ENT) outpatient clinics after going through various guidelines to make it safe in current scenario. These changes may inspire others to move toward safer work practices in their outpatient area to provide ENT consultations. The main changes were categorized into infrastructural changes, identification of frugal but effective personal protective equipment (PPE) for ENT, training for use of different level of PPE as per risk, new modus operandi, and new infection prevention measures. These changes had taken into account safety guidelines by Ministry of health and family welfare (MOHFW) government of India and various international associations specific to specialty. The modification and its advantages were presented.